The Role of External Factors on Actual Technology Use of Omni Channel Applications - Samiono, Bambang Eko; Pratiwi, Anggun; Sunarmo; Alam, Rahmat (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
This study aims to analyse the role of external factors (Job Relevance and Computer Self-Efficacy) on Actual Technology Use of Omni Channel Applications (What'sApps Business) in MSMEs in Sukabumi based on the concept of Technology Acceptance Model (TAM). Quantitative research methods are carried out using the basic Technology Acceptance Model (TAM) variables. The analysis was conducted using SEM-PLS. The sample set was 200 MSMEs in Sukabumi. Non-probability sampling techniques with purposive sampling were used for sampling. The findings in this study are the existence of the Omni Channel application (What'sApps Business) has been accepted by MSME in Sukabumi. This is evident from the direct and indirect effects of all variables involved in Actual Technology Use. The role of Job Relevance and Computer Self Efficacy variables also have a positive and significant influence on Perceived Ease of Use and Perceived Usefulness of respondents.